Self-fulfilling prophecies in the classroom: Teacher expectations, teacher feedback and student achievement. (April 2020) - Gentrup, Sarah; Lorenz, Georg; Kristen, Cornelia; Kogan, Irena
Abstract: This study investigated the link between teacher expectations and student learning, relying on longitudinal data from 64 classrooms and 1026 first-grade students in Germany. Further, based on a subsample of 19 classrooms with 354 students, we explored the mediating role of three characteristics of teacher feedback rated in video-recorded school lessons. The results showed that teacher expectations were inaccurate to some extent; that is, they did not entirely agree with students' current achievement, general cognitive abilities and motivations. In addition, this inaccuracy in teacher expectations significantly predicted students' end-of-year achievement, even after prior achievement, general cognitive abilities, motivation, and student background characteristics were considered. Specifically, inaccurately high teacher expectations were associated with greater achievement in reading and mathematics, whereas inaccurately low teacher expectations were associated with lower achievement in reading only. Furthermore, teacher feedback varied significantly with inaccurate teacher expectations but did not substantially mediate teacher expectancy effects. Highlights: Early teacher expectations predict student learning in the first year of schooling. Teacher expectancy effects are stronger in reading than in mathematics. Differential teacher expectations translate into varying teacher feedback. Teacher feedback does not substantially mediate teacher expectancy effects.